Environmental Applications of Boron‐Doped Diamond Electrodes: 1. Applications in Water and Wastewater Treatment. Issue 8 (28th March 2019) - Nidheesh, P. V.; Divyapriya, G.; Oturan, Nihal; Trellu, Clément; Oturan, Mehmet A.
Abstract: Over the past few decades, environmental applications of the boron‐doped diamond (BDD) electrode are reported to be vast and versatile. Applications of BDD electrodes in the field of electrochemical advanced oxidation processes (EAOPs) for the abatement of toxic persistent organic pollutants are significant, owing to the easy and effective way of treatment. This article focuses on highlighting and summarizing the applications of the BDD electrode for the treatment of different synthetic and real wastewaters, such as those involved in pharmaceuticals and personal care products, pesticides/herbicides, dyes, etc. We also review the processes and methodologies involving the synthesis of BDD electrodes and summarize the desirable characteristic features required for the application of EAOPs. Applications of BDD electrodes for the treatment of wastewater through different EAOPs, including anodic oxidation, electro‐Fenton, coupling processes such as electro‐Fenton pyrite, bioelectro‐Fenton, and their recent advancements are also discussed in detail. It envisages the greater potential for complete treatment of different toxic wastewater effluents. This Review shows that the application of BDD electrodes in the field of wastewater treatment is tremendous and proves to be a promising material for future perspectives. Abstract : Diamond standard : Boron‐doped diamond (BDD) electrodes are found to be effective for the generation of hydroxyl radicals in water and are more effective than other electrodes. The main applications of BDD‐based anodic oxidation and electro‐Fenton processes are reviewed in detail.